FINITE ELEMENT ANALYSIS OF LEAF SPRING AND REAR AXLE FOR REAR SUSPENSION - Anita Hase; Dr. Sanjay Zope; Prof. Amol Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
Leaf spring and rear axle are major parts of vehicle suspension system which is subjected to millions of varying stress cycles leading to fatigue failure. In a commercial light vehicles engine is placed at front or middle providing large space to the rear axle. Advantages of the new rear suspension design of the light commercial vehicle have been captured. In most of the vehicle Engine is placed at rear to have low engine noise and vibration inside cabin of vehicle. In This paper we are suggesting best material for leaf spring & rear axle .Oil tempered carbon steel and manganese silicon steel analyzed and found that oil tempered carbon steel is best for leaf spring of light duty vehicles. Similarly For rear axle such as Blue tempered and polished steel and forged alloy steel . According to results found in software analysis the best material for rear axle is forged alloy steel.